Chronicles of civil society in Assam and Meghalaya: converting girls and women from «bad to good» - Barnali Das; Rekha Pande (Ex Aequo: Revista da Associação Portuguesa de Estudos sobre as Mulheres)
This paper examines the standpoints and the approach of the stakeholders working towards combatting sex trafficking in Assam and Meghalaya, India, with the aim of understanding whether the selected stakeholders uphold a gender-sensitive conceptualization, understanding and approach towards sex trafficking. Such an approach is significant since it ensures that victims of sex trafficking are protected from further marginalization and exploitation. In contemplating the voices of the stakeholders, the paper shows that the implementation and execution of the anti-trafficking provisions are genderladen. It claims that, while putting the anti-trafficking provisions of prevention, rescue, rehabilitation and repatriation into action, the stakeholders do not differentiate between voluntary and forced sex work. The absence of this distinction results in the “forced rescue” of voluntary sex workers. This article therefore shows how stakeholders impose the idea of “normal womanhood” and constantly seek to control and regulate women’s sexuality.